Pharmacokinetic and bioequivalence study of two brands of valsartan tablets in healthy male volunteers - Zakeri-Milani, Parvin; Valizadeh, Hadi; Islambulchilar, Ziba; Nemati, Mahboob (Arzneimittelforschung, 2010)
Valsartan (CAS 137862-53-4) is an antihypertensive drug belonging to the family of angiotensin II receptor antagonists acting at the AT1 receptor, which mediates all known effects of angiotensin II on the cardiovascular system. In the present study, the pharmacokinetic parameters of two oral formulations of valsartan tablets were compared in a randomized, single oral dose, two-treatment crossover design in 24 healthy male volunteers under fasting conditions. After an overnight fast, the volunteers received 80 mg valsartan. Blood samples were collected up to 48 h and drug concentrations were determined by a reverse-phase HPLC method with fluorescence detection. Various pharmacokinetic parameters were determined from the plasma concentration-time curves of both formulations. The obtained values for test and reference products were 3 067.7 ± 1 281.7 and 3 304.3 ± 1 196.4 ng/ml for Cmax; 17 834.4 ± 7 083.8 and 18319.1 ± 7 800.7 ng · h/ml for AUC0–48; 18825.7 ± 7 553.2 and 19 172.2 ± 8 307.2 ng · h/ml for AUC0–∞, respectively. The 90% confidence intervals obtained by analysis of variance were 86.84–100.87% for Cmax and 93.43–115.54% for AUC0–t, which are within the acceptance range of 80–125%. Therefore it can be concluded that both products are bioequivalent in terms of rate and extent of drug absorption and therefore interchangeable.
Keywords: Angiotensin II receptor antagonist; Antihypertensive; CAS 137862-53-4; Valsartan, bioavailability, bioequivalence